2013
DOI: 10.1371/journal.pbio.1001699
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Cost of "Low-Cost" Whole Genome Sequencing: Framing the Health Policy Debate

Abstract: The future clinical applications of whole genome sequencing come with speculation and enthusiasm but require careful consideration of the true system costs and health benefits of the clinical uses of this exciting technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 32 publications
(27 reference statements)
1
62
0
Order By: Relevance
“…At the same time, sequencing costs have rapidly decreased, contributing to a rapid diffusion of NGS applications into clinical settings (2)(3)(4). Whereas only 10 years ago the sequencing costs of a million base pairs were approximately $1000, the costs are now below $0.10 (2,(5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, sequencing costs have rapidly decreased, contributing to a rapid diffusion of NGS applications into clinical settings (2)(3)(4). Whereas only 10 years ago the sequencing costs of a million base pairs were approximately $1000, the costs are now below $0.10 (2,(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…At the same time, sequencing costs have rapidly decreased, contributing to a rapid diffusion of NGS applications into clinical settings (2)(3)(4). Whereas only 10 years ago the sequencing costs of a million base pairs were approximately $1000, the costs are now below $0.10 (2,(5)(6)(7)(8). Several commercial parties claim to have broken the barrier of the $1000 genome (9,10 ), an accomplishment that would allow for large-scale clinical application, furthering our understanding of genetic diseases and ultimately contributing to personalized medicine in a major way (11 ).…”
mentioning
confidence: 99%
“…Despite those advances in cancer research, economic evidence supporting the application of high-throughput genomic technologies in everyday practice is lacking 7,8 . The accelerated pace with which high-throughput genomic assays and next-generation sequencing technologies are being used in cancer diagnostics threatens to outpace an assessment of the economic implications of changes in practice [9][10][11] . A recent rapid review of the cost-effectiveness of nextgeneration sequencing technologies, including wholegenome, whole-exome, and targeted capture sequencing, conducted by the Canadian Agency for Drugs and Technologies in Health, found that the economic evidence is currently insufficient to make definitive claims about the cost-effectiveness of next-generation sequencing technologies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The cost to sequence the human genome (encompassing 30,000 to 35,000 genes) is rapidly decreasing with the development of high-throughput sequencing technology [16,17]. With implications for current public health policies and delivery of care [18,19], analyzing genome-scale data for developing actionable recommendations in a timely manner is a significant challenge to the field of computational biology. Cost and time to deliver recommendations are crucial in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%